2017
DOI: 10.3390/md15060178
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin Sulfate-Rich Extract of Skate Cartilage Attenuates Lipopolysaccharide-Induced Liver Damage in Mice

Abstract: The protective effects of a chondroitin sulfate-rich extract (CSE) from skate cartilage against lipopolysaccharide (LPS)-induced hepatic damage were investigated, and its mechanism of action was compared with that of chondroitin sulfate (CS) from shark cartilage. ICR mice were orally administrated 200 mg/kg body weight (BW) of CS or 400 mg/kg BW of CSE for 3 consecutive days, followed by a one-time intraperitoneal injection of LPS (20 mg/kg BW). The experimental groups were vehicle treatment without LPS inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 45 publications
(47 reference statements)
2
19
0
1
Order By: Relevance
“…CS-containing extract isolated from skate cartilage reportedly reduces liver damage induced by lipopolysaccharide; however, the molecular target for the CS-containing extract was not known. 43 Using the pure CS oligosaccharides, we demonstrate the protective effect against histone- or lipopolysaccharide-induced organ damage with certainty. In addition to histones, other proinflammatory proteins, like high mobility group box 1 (HMGB1), play important roles in the pathology of sepsis.…”
Section: Discussionmentioning
confidence: 80%
“…CS-containing extract isolated from skate cartilage reportedly reduces liver damage induced by lipopolysaccharide; however, the molecular target for the CS-containing extract was not known. 43 Using the pure CS oligosaccharides, we demonstrate the protective effect against histone- or lipopolysaccharide-induced organ damage with certainty. In addition to histones, other proinflammatory proteins, like high mobility group box 1 (HMGB1), play important roles in the pathology of sepsis.…”
Section: Discussionmentioning
confidence: 80%
“…Известно, что фиксированная комбинация хондроитина и глюкозамина снижает уровень оксидативного стресса в течение уже 28 дней от начала терапии [18]. Активные формы кислорода, индуцированные ишемией хряща и субхондральной кости вследствие нарушения сосудистых паттернов, способствуют активации патологического внутриклеточного каскада ядерного фактора каппа B [19,20,21], который, в свою очередь, запускает транскрипцию генов MMPs, цитокинов, хемокинов, приводящих к деградации внеклеточного матрикса [22,23]. Более того, активное свободнорадикальное окисление способствует повреждению ДНК и формированию патологического фенотипа хондроцитов [24,25].…”
Section: Discussionunclassified
“…Although CS-A and CS-C (Figure 3) are still expressed in marine organisms, they do not possess the same observed and potential therapeutic applications outside of more commonplace use in osteoarthritis as the other CS sub-types (Figure 1A). CS-D, CS-E, and CS-K (Figure 3), and very rarely CS-L and CS-M (Table 1) have been shown to exhibit an array of other biomedical activities related to anti-inflammation [66,67], cancer and metastasis [25,68,69], neurology [52], and antipathogenesis [28]. These CS types are less commonly found than CS-A and CS-C in mammals, and more common in marine organisms (Table 1), but indications exist of their presence, although in minor portions, in tissues of terrestrial mammals [54,70,71].…”
Section: Csmentioning
confidence: 99%
“…These effects are highly mediated by CS’s interactions with pro-inflammatory enzymes and transcription factors related to attenuation of inflammatory response [78]. Jeong-Sook Noh et al demonstrated that in hepatic tissues CS-E produced noticeable protection against inflammatory and oxidative damage by lipopolysaccharides through down-regulation in TNF-α, IL-1β, COX-2, and iNOS hepatic inflammatory factors [66].…”
Section: Csmentioning
confidence: 99%